2014
DOI: 10.2188/jea.je20130070
|View full text |Cite
|
Sign up to set email alerts
|

Common Genetic Factors Influence Hand Strength, Processing Speed, and Working Memory

Abstract: BackgroundIt is important to detect cognitive decline at an early stage, especially before onset of mild cognitive impairment and dementia. Processing speed and working memory are aspects of cognitive function that are associated with cognitive decline. Hand strength is an inexpensive, easily measurable indicator of cognitive decline. However, associations between hand strength, processing speed, and working memory have not been studied. In addition, the genetic and environmental structure of the association b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 32 publications
0
9
1
Order By: Relevance
“…Our method employed a Bayesian hierarchical statistical approach and used a cognitive decision-making model to separate out different sources of variability in data. While previous studies made the simple assumption that observed heritability in response time is attributable solely to heritability in the speed of mental processing (Beaujean, 2005;Finkel & Pedersen, 2004;Kochunov et al, 2016;Luciano et al, 2001;Ogata et al, 2014;Posthuma et al, 2002;Vernon, 1989), we found greater genetic contribution to response caution than to underlying cognitive speed within the memory task assessed. Our results fall in line with the previous findings of Engelhardt et al (2016), who used psychometric testing to show that a strong genetic component exists within executive functions.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Our method employed a Bayesian hierarchical statistical approach and used a cognitive decision-making model to separate out different sources of variability in data. While previous studies made the simple assumption that observed heritability in response time is attributable solely to heritability in the speed of mental processing (Beaujean, 2005;Finkel & Pedersen, 2004;Kochunov et al, 2016;Luciano et al, 2001;Ogata et al, 2014;Posthuma et al, 2002;Vernon, 1989), we found greater genetic contribution to response caution than to underlying cognitive speed within the memory task assessed. Our results fall in line with the previous findings of Engelhardt et al (2016), who used psychometric testing to show that a strong genetic component exists within executive functions.…”
Section: Discussioncontrasting
confidence: 78%
“…Analysis of data from twins has supported the notion that there are heritable components to both general cognitive processes (e.g., intelligence) and the cognitive processes that underpin them (e.g., processing speed: Beaujean, 2005;Finkel & Pedersen, 2004;Kochunov et al, 2016;Luciano et al, 2001;Ogata, Kato, Honda, & Hayakawa, 2014;Posthuma, Mulder, Boomsma, & De Geus, 2002;Vernon, 1989). However, a limitation of the work so far is an untested assumption that response time is a pure reflection of underlying cognitive processing speed.…”
Section: Introductionmentioning
confidence: 99%
“…h 2 SNP for the mean response accuracy in the 2-back alone (that is, without correction for 0-back performance) and the false-response corrected d-prime condition were 31% with s.e.=0.138; P -value=0.006 and s.e.=0.140; P -value=0.01, respectively. Due to several reports linking processing speed to WM-related cognitive abilities, 25 , 26 we also investigated heritability of the mean reaction time in the 2-back condition ( h 2 SNP : 24% s.e.=0.142; P -value=0.04). A descriptive analysis of correlations between phenotypes shows strong intercorrelations between the three accuracy-related 2-back WM phenotypes ( r 2 >0.65), whereas correlation coefficients between the mean reaction time in the 2-back condition and the WM phenotypes are negligible ( r 2 <0.01) by means of shared phenotypic variance ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…A number of epidemiologic prospective studies have demonstrated an inverse association between late-life handgrip strength and cognitive function in elderly populations. [34][35][36][37] A scoping review revealed a clear relationship between lower handgrip strength and the progression of cognitive decline. 17 Likewise, lower late-life handgrip strength has been reported to be significantly associated with a greater risk of total dementia in several prospective studies of the elderly.…”
Section: Discussionmentioning
confidence: 99%